A new trinuclear cluster-based Cd(II) compound: photocatalytic property and nursing application values on the bacterial infection. Issue 1 (1st January 2021) - Hu, Yan; Ni, Jiao
ABSTRACT: A new Cd(II) coordination polymer with the formula of [(CH3 )2 NH2 ][Cd3 (NH2 -bdc)3 (btz)(H2 O)] n (1 NH2 -H2 bdc = 2-aminoterephthalic acid, Hbtz = 1 H-benzotriazole) was produced and then it was structurally characterized through powder X-ray diffraction (PXRD), the analysis of X-ray single-crystal diffraction, along with elemental analysis (EA). The photocatalytic property investigations indicate that compound 1 exhibits good activity for photodegradation of methyl violet (MV) with 60.7% of MV removal in 40 min under room temperature. Furthermore, the assessment of the compound's treatment activity and nursing application values on the bacterial infection was conducted and its corresponding mechanism was also studied. Evaluation of the in vitro hemolysis of the compound was determined by measuring the degree of red blood cell lysis and hemoglobin release. The effect of new compounds on the relative proliferation rate of L-929 cells was measured by MTT assay. The ELISA detection kit showed that the compound could reduce the TNF-α and IL-1β content released into plasma. Next, the inhibitory activity of the compound on the bacterial survival gene expression was also proved with real-time RT-PCR. The hemolysis rate of the new compound to blood is 3.4%, which is less than the standard 5%, which is non-hemolytic reaction. The compound also has no obvious cytotoxicity and has good cell compatibility.